2020
DOI: 10.1155/2020/4060648
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence in Inflammatory Bowel Disease Patients from Argentina: A Multicenter Study

Abstract: Background and Aim. Treatment adherence is a frequent problem in inflammatory bowel disease (IBD). No study has assessed adherence in Argentinian patients with IBD. The aim of this study was to determine inadequate adherence to oral and parenteral therapies in patients with IBD from Argentina and to identify factors associated with it. Methods. A multicenter cross-sectional study involving seven referral centers from three cities of Argentina was undertaken. Patients with a diagnosis of ulcerative colitis (UC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Mikocka-Walus et al [64] identified increases in medication usage after the introduction of an IBD dedicated nurse. Furthermore, the role of IBD nurses is an essential component of integrated models of care (IMC); a model of care for IBD that can increase healthcare access, improve medication adherence, and improve other healthcare outcomes [65][66][67]. In fact, IMC for IBD are recommended due to their multiple positive impacts on patient outcomes [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Mikocka-Walus et al [64] identified increases in medication usage after the introduction of an IBD dedicated nurse. Furthermore, the role of IBD nurses is an essential component of integrated models of care (IMC); a model of care for IBD that can increase healthcare access, improve medication adherence, and improve other healthcare outcomes [65][66][67]. In fact, IMC for IBD are recommended due to their multiple positive impacts on patient outcomes [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Biologic use was seen in 24.8% (111/447) and 33.3% (45/135) of the patients with UC and CD, respectively ( p = 0.06). 28 Inadequate adherence to biologics was seen in 15.3% of patients (19.5% in UC versus 24% in CD, p = 0.6). The risk of inadequate adherence to biologics was significantly lower than oral 5-aminosalicylates (OR 4.1; 95% CI 2.7–6.3) and thiopurines (OR 1.7; 95% CI 1.1–2.7).…”
Section: Biological Therapies Penetration In Latammentioning
confidence: 92%
“…The risk of inadequate adherence to biologics was significantly lower than oral 5-aminosalicylates (OR 4.1; 95% CI 2.7–6.3) and thiopurines (OR 1.7; 95% CI 1.1–2.7). 28 …”
Section: Biological Therapies Penetration In Latammentioning
confidence: 99%
“…Such diseases possess a high prevalence in Europe and are increasing at a high incidence rate since the ’90s in newly industrialized countries, such as Brazil and Taiwan ( Ng et al, 2017 ). Treatment options for IBDs are commonly not well accepted or tolerable for a great part of patients ( Horne et al, 2009 , Lasa et al, 2020 , Pieper et al, 2009 ), suggesting the need for studies capable of proving new effective options. From our knowledge, four studies to date have attested the positive effects of hawthorn in IBDs; however, these investigations used the fruits, not the leaves or flowers, and distinct hawthorn species ( Fujisawa et al, 2005 , Guo et al, 2021 , Liu et al, 2020 , Malekinejad et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%